PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DITINJAU DARI PERSPEKTIF EKONOMI ISLAM (SURVEI PADA KANTOR CAMAT KECAMATAN KAMPAR KIRI HULU) - Edi Haryono; Marabona Munthe (Jurnal Daya Saing, 2025)
This study aims to analyze the influence of leadership style on employee performance at the Kampar Kiri Hulu Subdistrict Office and to examine it from the perspective of Islamic economics. Leadership is one of the most important factors affecting employee effectiveness in achieving organizational goals. From the Islamic economic perspective, leadership is not merely oriented toward organizational achievement but also emphasizes the values of trustworthiness (amanah), justice, responsibility, and exemplary conduct. This research employed a quantitative approach using a survey method. The population consisted of all employees of the Kampar Kiri Hulu Subdistrict Office, with a saturated sampling technique applied to select respondents. Data were collected through questionnaires and analyzed using simple linear regression analysis. The results indicate that leadership style has a positive and significant effect on employee performance. The better the leadership style implemented, the higher the level of employee performance achieved. Viewed from the perspective of Islamic economics, the leadership style practiced reflects Islamic leadership values such as trustworthiness (amanah), consultation (shura), justice, and responsibility, which contribute to improving employee motivation and productivity. Therefore, strengthening Islamic leadership values should be continuously promoted to enhance public service quality and organizational performance